Critical illness in the returning traveller. (February 2022) - Howells, Phillip; Laird, Steven; Johnston, Andrew McD; Billyard, Thomas
A 70 year old man, who had recently travelled in rural Iraq, presented with fevers, rigors, and developed multiorgan failure. An extensive range of diagnostic tests was undertaken in an attempt to identify the cause. He was treated with multi-organ support and a number of antibiotics. Critical illness in the returning traveller presents a number of challenges on the ICU: obtaining adequate history, the potentially broad differential diagnosis, the requirement for numerous and sometimes specialised investigations and risks of infection transmission to staff and other patients. Travellers are more often elderly, more likely to have comorbidities and immunosuppression whilst global disease patterns are changing. Particular consideration should be given to unusual infections and venous thromboembolic disease from prolonged immobility whilst in transit, alongside more commonly encountered diseases. Antimicrobial resistance may be encountered and appropriate infection control is essential for the protection of patients, staff and others. Specialist support is available in the UK via the Imported Fever Service, especially for High Consequence Infectious Diseases. Consideration of non-infectious causes of fever and critical illness in returning travellers is also warranted. Crucially, a multidisciplinary team approach with thorough information gathering, repeated clinical review and judicious use of investigations are essential for optimal patient care.